Internal CSR practices within the SME sector in Cyprus from the employees' perspective - challenges and prospects - Papasolomou, Ioanna; Kountouros, Haris; Melanthiou, Yioula (My University, 2018)
This paper examines the results of a recent study into four domains of internal corporate social responsibility (CSR) practices within small and medium-sized companies in Cyprus from the employees' perspective. This perspective gives an added insight into the developing CSR practices in Cyprus, revealing interesting findings about the sufficiency (or not) of current practices. Looking into the results of the study, as well as into a number of policy initiatives considered in the relevant national action plan on CSR, we seek to draw some conclusions on the prospects for further developing internal CSR practices across SMEs. We argue that a more active policy framework is needed. Considering the very small size of most Cypriot companies, current, or foreseen, legal requirements relevant to CSR do not apply to the majority of Cypriot businesses. This very fact raises a particular challenge for the development of CSR practices on the island. In light of this, we argue that voluntary CSR initiatives remain of primary importance, yet these should be developed within a broader framework which promotes cooperation between the various stakeholders.
Keywords: employee training and personal development; Cypriot SMEs; internal CSR; health and safety in the workplace; organisational justice and fairness; work-life balance